Fine-Crush Straw Returning Enhances Dry Matter Accumulation Rate of Maize Seedlings in Northeast China - Jiale Zhao; Xiaogeng Wang; Jian Zhuang; Yongjian Cong; Yun Lu; Mingzhuo Guo (Agronomy, 2021)
In the conventional straw returning operation, the maize straw is broken into pieces of about 10 cm and degraded naturally in the farmland. Under the conventional straw returning mode, maize straw does not easily decompose quickly in cold climate conditions, which can cause a significant decrease in the dry matter accumulation rate of next maize seedlings. Therefore, it is difficult to popularize conventional straw returning in the maize-growing regions of Northeast China. In order to solve the above-mentioned problems, a new agronomic technology of straw returning is proposed in this study, and a corresponding Bionic Straw Fine Crusher is developed to match the agronomic requirements. The key function of fine-crush straw returning is to significantly increase the contact area between the straw pith and the external environment by significantly shortening the crushing length, thus accelerating the rate of straw decomposition. In this study, the differences in operational effects between fine-crush straw returning, conventional straw returning, and no returning are clarified through 6 consecutive years of field experiments. At the same time, statistical analysis of the experimental data reveals the influence of fine-crush straw returning on the dry matter accumulation of maize at the seedling stage under the conditions of different returning modes, and determines the optimal agronomic parameter combination. The results of this study show that fine-crush straw returning significantly increased the decomposition rate, soil organic matter content, and soil accumulated temperature, thus creating a seedbed more favorable for maize seedling development. The experimental results showed that the optimal crushing length values of fine-crush straw returning were 1.5 cm, 3 cm, and 1.5 cm under mulching returning, shallow burial returning, and deep tillage returning conditions, respectively. Compared with conventional straw returning and no returning operations, the fine-crush straw returning operation can increase the maximum seedling dry matter accumulation of the maize crop by 5.1 g/plant and 2.8 g/plant (shallow burial), 4.2 g/plant and 1.8 g/plant (deep tillage), and 4.3 g/plant and 1.9 g/plant (mulching returning). The findings of this study may provide a viable new agronomic technology to accelerate the spread of straw returning in maize-growing areas of Northeast China.